Changes in cytokine and chemokine expression distinguish dysthymic disorder from major depression and healthy controls. (February 2017) - Ho, Pei-Shen; Yen, Che-Hung; Chen, Chun-Yen; Huang, San-Yuan; Liang, Chih-Sung
Abstract: An important area of uncertainty is the inflammatory degree to which depression occurring as part of dysthymic disorder may differ from major depression. Using a 27-plex cytokine assay, we analyzed the serum of 12 patients with dysthymic disorder, 12 with major depression, and an age-, sex-, and body mass index-matched control group of 20 healthy volunteers. We observed that patients with dysthymic disorder exhibited aberrant cytokine and chemokine expression compared with healthy controls and patients with major depression. The levels of interferon-γ-induced protein 10 highly predicted dysthymic disorder. Network analyses revealed that in patients with dysthymic disorder, the vertices were more sparsely connected and adopted a more hub-like architecture, and the connections from neighboring vertices of interleukin 2 and eotaxin-1 increased. After treatment with the same antidepressant, there was no difference between dysthymic disorder and major depression regarding any of the cytokines or chemokines analyzed. For dysthymic disorder, changes in the levels of interferon-γ-induced protein 10 and macrophage inflammatory protein-1α correlated with depression improvement. The findings suggest that the cytokine milieu in dysthymic disorder differs either at the level of individual expression or in network patterns. Moreover, chemokines play an important role in driving the pathophysiology of dysthymic disorder. Graphical abstract: Highlights: Dysthymia had more widespread differential expression in cytokines and chemokines. Changes in IP-10 and MCP-1α correlated with depression improvement in dysthymia. The levels of IP-10 highly predicted dysthymia. The cytokine network of dysthymia adopted a more hub-like architecture. The interconnections of IL-2 and eotaxin-1 in network increased in dysthymia